Red hot mama : the life of Sophie Tucker - Sklaroff, Lauren Rebecca (University of Texas Press, 2018)
The "First Lady of Show Business" and the "Last of the Red Hot Mamas," Sophie Tucker was a star in vaudeville, radio, film, and television. A gutsy, song-belting stage performer, she entertained audiences for sixty years and inspired a host of younger women, including Judy Garland, Carol Channing, and Bette Midler. Tucker was a woman who defied traditional expectations and achieved success on her own terms, becoming the first female president of the American Federation of Actors and winning many other honors usually bestowed on men. Dedicated to social justice, she advocated for African Americans in the entertainment industry and cultivated friendships with leading black activists and performers. Tucker was also one of the most generous philanthropists in show business, raising over four million dollars for the religious and racial causes she held dear. Drawing from the hundreds of scrapbooks Tucker compiled, Red Hot Mama presents a compelling biography of this larger-than-life performer. Lauren Rebecca Sklaroff tells an engrossing story of how a daughter of Russian Jewish immigrants set her sights on becoming one of the most formidable women in show business and achieved her version of the American dream. More than most of her contemporaries, Tucker understood how to keep her act fresh, to change branding when audiences grew tired and, most importantly, how to connect with her fans, the press, and entertainment moguls. Both deservedly famous and unjustly forgotten today, Tucker stands out as an exemplar of the immigrant experience and a trailblazer for women in the entertainment industry